The Fog of Peace: Comparing U.S. and UN Approaches to Conflict Management in Nepal - Gross, Joshua R. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: An engagement strategy-employed to change an adversary's perception of its self-interest while proposing attractive alternatives to its current course of action-has been the rationale behind numerous UN-led mediation efforts with non-state armed groups. Traditionally, the UN has talked to groups that are considered terrorists by the U.S. Alternatively, the U.S. rarely chooses to overtly engage armed groups. In the aftermath of Nepal's ten-year civil war, U.S. and UN approaches to conflict management were defined by a fundamental disagreement over the efficacy of engagement with the Unified Communist Party of Nepal (Maoist). The Maoists have been a specially designated terrorist entity by the U.S. since 2003. Neither the U.S.' non-recognition strategy nor the U.N.'s engagement strategy succeeded in changing the Maoists' intentions, capabilities or behavior. The mindset of counter-terrorism impeded the U.S.' ability to contextually analyze the likelihood that the Maoists could moderate and evolve into a legitimate political party. The Maoists' terrorist designation was the primary obstacle that prevented the U.S. from playing a more constructive role in Nepal's peace process. Labeling a group a terrorist entity and cutting off the possibility for engagement can become a self-fulfilling prophecy, neutralizing incentives for an armed group to undergo the difficult transformation into a legitimate and nonviolent political party. Alternatively, the United Nations pursued a strategy of inducement and socialization, but failed to appropriately respond to Maoist actions that contravened the letter and the spirit of the peace process. The United Nations Mission in Nepal was established as a political mission with a narrow mandate, lacking both armed peacekeepers and the power to act as an official mediator. The UN's approach to conflict management in Nepal suggests that they did not anticipate the possibility that the Maoists had entered into negotiations in bad faith.